Study on influencing parameters and long-term operation of electrocoagulation phosphorus removal from small rural domestic sewage. (12th April 2023) - Jiang, Chunfeng; Liu, Yanqing; Zhang, Chong; Li, Xianning
Abstract: Excessive discharge of phosphorus can produce eutrophication in aquatic environments, damaging public health, the living environment, and the economy. The conventional mechanical–biological phosphorus removal methods are not suitable for small rural domestic sewage due to the features of small scale, scattered distribution, intermittent emission, and large fluctuation. This work evaluated electrocoagulation (EC) with industrial steel as electrodes on small rural domestic sewage. Results showed that the best performance was achieved at a current density of 1 mA/cm 2, electrode distance of 2 cm, electrode number of 2, pH of 7, and Hydraulic Retention Time of 30 min, respectively. Under optimum conditions, the EC process removed 93.91% phosphorus while consuming around 0.25 kWh/m 3 of electricity. In addition, the electrode passivation of EC was further investigated; the long-term research found that the phosphorus removal efficiency only decreased by 4.34% after 10 days of continuous flow operation, and the operational energy consumption was 0.07 kWh/m 3 at a Cl – concentration of 500 mg/L. HIGHLIGHTS: EC was developed to remove phosphorus from small rural domestic sewage. Optimization of the EC process can effectively reduce energy consumption. Current density and HRT were positively correlated with removal efficiency. Adding Cl – can inhibit electrode passivation. Graphical Abstract